EVALUASI PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) PADA WORKSHOP DI PT LEMATANG COAL LESTARI (LCL) MUARA ENIM - Niky Oktariza; Ridho Yovanda; Aris Susilo (Jurnal Humaniora & Sosial Sains, 2025)
PT LCL's coal mining activities in Muara Enim, which intensively utilize heavy equipment, generate Hazardous and Toxic Materials (B3) waste from the workshop area. Therefore, proper management is crucial to prevent environmental and health risks. This study aims to identify the types of B3 waste generated and evaluate the level of compliance of its management system based on Ministerial Regulation (PERMEN LHK) No. 6 of 2021. Using a descriptive evaluative method, data were collected through direct observation in the workshop and Temporary Storage Area (TPS), interviews with personnel, and analysis of documents such as logbooks and manifests. The identification results indicate that the dominant B3 waste includes used oil, used filters, used batteries, contaminated rags, and used B3 packaging. The company's management process is structured, from containerization and collection to storage at the TPS before being handed over to a licensed third-party processor. The evaluation concluded that most management aspects, such as TPS construction, waste type separation, and third-party contracts, comply with regulations. However, minor deficiencies were identified that require improvement, particularly in the completeness of labeling on each waste container and suboptimal housekeeping practices within the TPS.